The small strains behaviour of laterite soil / Tengku Anita Raja Hussin - Raja Hussin, Tengku Anita (1997)
This study is primarily concerned with the measurement of small strains of soil. Experience has shown that the strain in the ground was actually very small. A programme of triaxial compression tests was conducted on re-constituted compacted soil samples taken from a site in Shah Alam, Selangor Darul Ehsan. The samples were prepared at a moisture content equivalent to it 95 % of its maximum dry density on the wet side of optimum water content. The samples were instrumented with local axial strain devices mounted directly on the soil. Recent work has demonstrated that soils can be equally as brittle as rocks and that the understanding of their behaviour strains below 0.05 % is very important. Indeed, K-0 normally consolidated clays may reach peak strength at strains as low as 0.1 %. Even when the behaviour is not brittle, the strains prior to yielding are usually very small. From the study, the soil stifmess at small strains which is reflected the value of Young Modulus (E), is actually higher than the soil stiffness measured in the laboratory. This is followed that the value of E used in design should be based on the actual E value in small strains test.